2019
DOI: 10.1166/mex.2019.1548
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced slump retention using polycarboxylate superplasticizers obtained by micro-crosslinking reaction

Abstract: In this paper, a facile method was adopted to synthesize polycarboxylate (PC) superplasticizers which rendered excellent initial fluidity and workability of mortar in 1 hour. Micro-crosslinking was introduced in the PC molecules and the ester groups in crosslinker can form carboxyl groups in the hydration solution of cement. The micro-crosslinked PC (MPC) superplasticizer was synthesized from butenyl alkylenepolyoxyethylene-polyoxypropylene ether, sodium methacrylate, acrylic acid with trimethylolpropane tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Their results showed that the fluidity of this crosslinked superplasticizer diminished from its original value by only ~10 mm in 2 h, while the spread of a common polycarboxylate superplasticizer diminished by nearly 50 mm during the same duration, which demonstrated that the crosslinked superplasticizer had a superb slump retention effect. In addition, a similar result was also obtained by Cai et al, 20 they found that a crosslinked polycarboxylate superplasticizer could effectively improve the fluidity of mortar and maintain its fluidity as well.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Their results showed that the fluidity of this crosslinked superplasticizer diminished from its original value by only ~10 mm in 2 h, while the spread of a common polycarboxylate superplasticizer diminished by nearly 50 mm during the same duration, which demonstrated that the crosslinked superplasticizer had a superb slump retention effect. In addition, a similar result was also obtained by Cai et al, 20 they found that a crosslinked polycarboxylate superplasticizer could effectively improve the fluidity of mortar and maintain its fluidity as well.…”
Section: Introductionsupporting
confidence: 80%
“…13,14 In practice, COO À ions are usually introduced as the anionic groups in polycarboxylate superplasticizers. [15][16][17][18] Crosslinked superplasticizers are a new type of water reducing agent, 6,[19][20][21] which have attracted the attention of researchers and have been in increasing demand for industrial applications. These superplasticizers are usually obtained via the copolymerization of crosslinkers, anionic acrylates that act as monomers, and polyethers that provide long side-chains.…”
Section: Introductionmentioning
confidence: 99%
“…At a fixed molecular weight, the surface-occupied area became smaller for star-shaped PCEs with an increase in arm numbers, resulting in an increase in the adsorption free energy. In addition, many papers have reported cross-linked PCEs with different cross-linking monomers [142][143][144][145][146][147] with varied numbers of double bonds. Some reports have shown that slight cross-linking can improve the adsorption and thus the initial flowability of cement paste.…”
Section: Topological Structure and Polymer Molecular Framementioning
confidence: 99%
“…Etsuo et al controlled slump loss by introducing the diethylene glycol diacrylate as a crosslinking agent in PC copolymers [15]. Cai et al found that a crosslinked polycarboxylate superplasticizer could effectively improve the fluidity of mortar and maintain its fluidity as well [16]. Liu et al reported the synthesis of the CLPCs.…”
Section: Introductionmentioning
confidence: 99%